PERGESERAN MITOLOGI PESANTREN DI ERA MODERN - Arif Junaidi (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2011)
The main problem of this study is how to root, pattern and function of beliefs about karamah of the kiai pesantren Futuhiyyah Mranggen Demak and the extent of the shift of mythology that occurred at the school in line with the social changes in the modern era. This study is a field research. The paradigm used in this study is a qualitative paradigm, because the study intended to find meaning. The findings of this study is that the lives of the kiai in the pesantren Futuhiyyah also widely covered by the myths of “kiaiship”, it is a belief that the kiai has karamah.